Population characteristics and self-assessment of speaking and singing voice in Polish contemporary commercial music singers—an exploratory, cross-sectional study - Morawska, Joanna; Pietruszewska, Wioletta; Politański, Piotr; Niebudek-Bogusz, Ewa (Frontiers in Public Health, 2024)
Background: The domination of the Contemporary Commercial Music (CCM) industry in music markets has led to a significant increase in CCM performers. Performing in various singing styles involves exposing CCM singers to risk factors potentially leading to voice problems. This necessitates the consideration of CCM singers in the Occupational Health framework. The aim of the present research was threefold. First, it sought to profile the Polish CCM singers. Second, it was designed to explore the prevalence of self-reported voice problems and voice quality in this population, in both speech and singing. Third, it aimed to explore the relationships between voice problems and lifetime singing involvement, occupational voice use, smoking, alcohol consumption, vocal training, and microphone use, as potential voice risk factors. Material and Methods: An online survey included socio-demographic information, singing involvement characteristics, and singers' voice self-assessment. The prevalence of voice problems was assessed by the Polish versions of the Vocal Tract Discomfort Scale (VTDS) and the Singing Voice Handicap Index (SVHI). Also, a self-reported dysphonia symptoms protocol was applied. The perceived overall voice quality was assessed by a Visual Analogue Scale (VAS) of 100 mm. Results: 412 singers completed the survey. Nearly half of the studied population declared lifetime singing experience over 10 years with an average daily singing time of 1 or 2 hours. 283 participants received vocal training. For 11.4% of respondents, singing was the primary income source, and 42% defined their career goals as voice-related. The median scores of the VTDS were 11.00 (0-44) and 12.00 (0-40) for the Frequency and Severity subscales respectively. The median SVHI score of 33 (0-139) was significantly higher than the normative values determined in a systematic review and meta-analysis (2018). Strong positive correlations were observed between SVHI and both VTD subscales:( p<0.001). The relationships between most of the other variables studied were weak or negligible. Conclusion: The examined CCM singers exhibited substantial diversity with regard to musical genre preferences, aspirations pertaining to singing endeavors, career affiliations, and source of income. Singing voice assessment revealed a greater degree of voice problems in the examined cohort than reported in the literature.